(2/3 + 2-10(4))²
asked by guest on Jan 28, 2025 at 4:08 pm
You asked:
MathBot Answer:
(23+2−10⋅4)2=125449=1393.7‾{\left( \frac{2}{3} + 2 - 10 \cdot 4 \right)}^{2} = \frac{12544}{9} = 1393.\overline{7}(32+2−10⋅4)2=912544=1393.7
(23+2−10⋅4)2=(23+2−10⋅4)2=(23+2−40)2=(83−40)2=(−1123)2=125449\begin{aligned}{\left( \frac{2}{3} + 2 - 10 \cdot 4 \right)}^{2}& = \left(\frac{2}{3} + 2 - 10 \cdot 4\right)^{2}\\& = \left(\frac{2}{3} + 2 - 40\right)^{2}\\& = \left(\frac{8}{3} - 40\right)^{2}\\& = \left(- \frac{112}{3}\right)^{2}\\& = \frac{12544}{9}\end{aligned}(32+2−10⋅4)2=(32+2−10⋅4)2=(32+2−40)2=(38−40)2=(−3112)2=912544